Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.molcel.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of an ERAD Pathway Mediated by the ER-Resident Protein Disulfide Reductase ERdj5

Abstract: ER-associated degradation (ERAD) is an ER quality-control process that eliminates terminally misfolded proteins. ERdj5 was recently discovered to be a key ER-resident PDI family member protein that accelerates ERAD by reducing incorrect disulfide bonds in misfolded glycoproteins recognized by EDEM1. We here solved the crystal structure of full-length ERdj5, thereby revealing that ERdj5 contains the N-terminal J domain and six tandem thioredoxin domains that can be divided into the N- and C-terminal clusters. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
126
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 34 publications
4
126
0
1
Order By: Relevance
“…Using a set of ERdj5 mutants in which only one CXXC motif remained intact, we found that SERCA2b preferentially bound to ERdj5 via Trx3 and Trx4 (Fig. 1D), which have significant reductase activity and are hence involved in ERAD (13). This was more directly shown using the ERdj5/CA4 mutant, in which the CXXC motif in the Trx4 domain was mutated to CXXA and other CXXCs to AXXA.…”
Section: Er-resident Reductase Erdj5mentioning
confidence: 79%
See 4 more Smart Citations
“…Using a set of ERdj5 mutants in which only one CXXC motif remained intact, we found that SERCA2b preferentially bound to ERdj5 via Trx3 and Trx4 (Fig. 1D), which have significant reductase activity and are hence involved in ERAD (13). This was more directly shown using the ERdj5/CA4 mutant, in which the CXXC motif in the Trx4 domain was mutated to CXXA and other CXXCs to AXXA.…”
Section: Er-resident Reductase Erdj5mentioning
confidence: 79%
“…Human SERCA2b cDNA was amplified by PCR from the Matchmaker Pretransformed Human HeLa library (Clontech) and subcloned into pcDNA3.1. Mouse ERdj5/WT and other ERdj5 mutants (AA, CA, H63A, C1, C2, C3, and C4) were constructed as described previously (12,13). The SERCA2b C875AC887A (SERCA2b/AA) and R923KR988K (SERCA2b/KK) double mutants were generated using the QuikChange site-directed mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations